1984
DOI: 10.1073/pnas.81.3.753
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines that bind at peripheral sites inhibit cell proliferation.

Abstract: The specific binding of benzodiazepines (BZDs) has been observed in many tissues and cell types and can be pharmacologically separated into two classes. The first and most studied are the central-type receptors in brain that are thought to mediate the known clinical effects of the BZDs (1-3). The other class is the peripheral-type binding site found in a variety of tissues and cells, including kidney (4, 6), heart (5, 6), platelets (7), mast cells (8), lymphocytes (9), many cell lines (10), and brain (11,12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0
5

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(89 citation statements)
references
References 13 publications
4
80
0
5
Order By: Relevance
“…Our laboratory, as well as others, has previously shown that PBR ligands regulate cell proliferation. [7][8][9][10][11][13][14][15][16][17] The in vivo behavior of the cells, however, differs from their in vitro behavior where no differences in the rates of cell proliferation between the MDA-231 PH and PL is seen. This may be due to a minimum of PBR levels required for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory, as well as others, has previously shown that PBR ligands regulate cell proliferation. [7][8][9][10][11][13][14][15][16][17] The in vivo behavior of the cells, however, differs from their in vitro behavior where no differences in the rates of cell proliferation between the MDA-231 PH and PL is seen. This may be due to a minimum of PBR levels required for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Increased expression of PBR has been found in numerous tumor types and PBR has been shown to regulate the differentiation state and proliferation rates of several cancer cell lines. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Over the past several years our laboratory has examined the role of PBR in breast cancer using the MDA-231 cell line. While examining MDA-231 cells from various origins we observed variations in their PBR levels.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that PBR is a high affinity cholesterol binding protein [12,13]. There are studies showing abundance of PBR in tumor cells and also specifically on nuclear membrane of tumor cells [14][15][16][17][18]. The subunits of PBR act as cholesterol receptor as well as cholesterol channel.…”
Section: Introductionmentioning
confidence: 99%
“…Receptores periféricos de BZDs (RPBs) foram identificados em tecidos endócrinos, fígado, rins, pulmão e testículos (Gavish et al, 1999; Ruff et al, 1985;Wang et al, …”
Section: Introductionunclassified
“…Os BDZs apresentam propriedades miorrelaxantes, ansiolíticas e sedativas devido à sua alta afinidade com sítios específicos de ligação no sistema nervoso central -os chamados receptores centrais de BZD (RCBs). Desta maneira, os BZDs constituem uma das classes de drogas mais freqüentemente prescritas e consumidas no Brasil, Europa e EUA (Ruiz et al, 1993).Receptores periféricos de BZDs (RPBs) foram identificados em tecidos endócrinos, fígado, rins, pulmão e testículos (Gavish et al, 1999; Ruff et al, 1985;Wang et al, …”
unclassified